THE EFFECT OF PROBLEM BASED LEARNING (PBL) MODEL ON PROBLEM SOLVING ABILITY OF STUDENTS AT SMA NEGERI 14 MEDAN - Fadhilah, Maulidatul (INPAFI (Inovasi Pembelajaran Fisika), 2023)
This study aims to determine the effect of applying the Problem Based Learning (PBL) learning model on problem solving abilities of students at SMA Negeri 14 Medan. The research method used is quantitative research with quasi-experiment non-equivalent control group design. The sample was selected using purposive sampling. The experimental class consisted of 25 students from class X IPA 4, while the control class consisted of 25 students from class X IPA 2. Data collection for this study was conducted using a pretest and posttest.  The results showed that the average pretest score of students in the experimental class was 46 and the average posttest score was 80, while in the control class, the average student pretest score was 45 and the average score was posttest average of 52. The results of hypothesis testing using a one-sample t-test indicated that tcount>ttable or 17.8016>1.6759 so it can be concluded that the problem based learning (PBL) model has a positive effect to increase the problem solving abilities of students